Knockdown of the ADHD Candidate Gene Diras2 in Murine Hippocampal Primary Cells. Issue 4 (February 2021) - Grünewald, Lena; Chiocchetti, Andreas G.; Weber, Heike; Scholz, Claus-Jürgen; Schartner, Christoph; Freudenberg, Florian; Reif, Andreas
Objective: The DIRAS2 gene is associated with ADHD, but its function is largely unknown. Thus, we aimed to explore the genes and molecular pathways affected by DIRAS2 .Method: Using short hairpin RNAs, we downregulated Diras2 in murine hippocampal primary cells. Gene expression was analyzed by microarray and affected pathways were identified. We used quantitative real-time polymerase chain reaction (qPCR) to confirm expression changes and analyzed enrichment of differentially expressed genes in an ADHD GWAS (genome-wide association studies) sample.Results: Diras2 knockdown altered expression of 1, 612 genes, which were enriched for biological processes involved in neurodevelopment. Expression changes were confirmed for 33 out of 88 selected genes. These 33 genes showed significant enrichment in ADHD patients in a gene-set-based analysis.Conclusion: Our findings show that Diras2 affects numerous genes and thus molecular pathways that are relevant for neurodevelopmental processes. These findings may further support the hypothesis that DIRAS2 is linked to etiological processes underlying ADHD.